Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1993
DOI: 10.1002/pro.5560021003
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structures of the myristylated catalytic subunit of cAMP‐dependent protein kinase reveal open and closed conformations

Abstract: Three crystal structures, representing two distinct conformational states, of the mammalian catalytic subunit of CAMP-dependent protein kinase were solved using molecular replacement methods starting from the refined structure of the recombinant catalytic subunit ternary complex (Zheng, J., et al., 1993a, Biochemistry 32,2154-2161). These structures correspond to the free apoenzyme, a binary complex with an iodinated inhibitor peptide, and a ternary complex with both ATP and the unmodified inhibitor peptide. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
320
2
2

Year Published

1996
1996
2010
2010

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 305 publications
(334 citation statements)
references
References 49 publications
10
320
2
2
Order By: Relevance
“…(d) KSMP was found to cleave the Csubunit in its native conformation but not if the kinase is pre-denatured (2). (e) It distinguishes between the "open" and "closed" conformations of the C-subunit (4) that were recently identified by x-ray crystallography of this kinase (5).…”
mentioning
confidence: 99%
“…(d) KSMP was found to cleave the Csubunit in its native conformation but not if the kinase is pre-denatured (2). (e) It distinguishes between the "open" and "closed" conformations of the C-subunit (4) that were recently identified by x-ray crystallography of this kinase (5).…”
mentioning
confidence: 99%
“…Myristoylation of many proteins is thought to represent a mechanism for reversible membrane association (26 -28). It is believed that the hydrophobic nature of myristate allows it to associate directly with membrane lipids, but there are proteins, such as mammalian cAMP-dependent kinase, in which myristoylation has no membrane-targeting function, but is instead important for structural stabilization (29). In some cases, it has been reported that myristate interacts with a specific membrane protein, thus mediating a targeted protein-protein interaction (30).…”
Section: Discussionmentioning
confidence: 99%
“…It is a close approximation of the conformation adopted by PKA at the moment the phosphotransfer is taking place and is merely identical to the PKA-ATP complex structure. The same group showed that the N-and Clobes of PKA can rotate relative to each other around Gly125 in the hinge region [12], a short strand connecting the two lobes opening the catalytic cleft. This movement displaces the catalytic amino acids from the enzymatically competent conformation they adopt in the closed structure described above.…”
Section: Kinase Conformationsmentioning
confidence: 99%
“…NMR experiments in the presence and absence of myristate suggest the existence of a similar binding site in phosphorylated Src [64]. Several other kinases such as p38a [68] and PKA [12] have also been shown to bind lipids, but the biological meaning of this event is not yet clear. Mutations affecting SH domain binding can cause diseases by disrupting kinase regulation [69].…”
Section: Keeping Kinases Inactivementioning
confidence: 99%